2023
DOI: 10.1080/10402004.2023.2235395
|View full text |Cite
|
Sign up to set email alerts
|

Power Losses of Oil-Jet Lubricated Ball Bearings With Limited Applied Load: Part 2—Experiments and Model Validation

F. de Cadier de Veauce,
L. Darul,
Y. Marchesse
et al.

Abstract: This paper presents an experimental study on load independent power losses in oil jet lubricated deep groove ball bearings. These experiments were performed under different operating conditions. Rotational speed, lubricant temperature, oil flow rate and rolling element bearings dimensions were varied to quantify their influence on power losses. A load-independent power losses model for rolling element bearings has been proposed in a companion paper (Darul et al., 2023, "Power Losses of Oil-Jet Ball Bearings wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…On the other hand, it has been shown by Darul et al [6] that unloaded BB in DGBB must also be considered in the IVR regime to accurately predict REB power losses. This study also showed that, for moderate speeds (N•dm product less than 10 6 ) and low applied loads (Fr < 5% C 0 ), most of the power losses are due to hydrodynamic rolling [21]. This study was carried out on radially loaded DGBB.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, it has been shown by Darul et al [6] that unloaded BB in DGBB must also be considered in the IVR regime to accurately predict REB power losses. This study also showed that, for moderate speeds (N•dm product less than 10 6 ) and low applied loads (Fr < 5% C 0 ), most of the power losses are due to hydrodynamic rolling [21]. This study was carried out on radially loaded DGBB.…”
Section: Introductionmentioning
confidence: 88%
“…The objective is to estimate the power dissipation of the support block as a function of speed, loads and outer ring temperatures. As explained in [21], a calibration block is used instead of the measurement one. This block has two lip seals and two oil-bath lubricated REBs which are identical to the ones used in the support blocks (DGBB).…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation